Partial anticipation, the flow of information and the economic impact of corporate debt sales - Chaplinsky, S.; Hansen, R. S. (Review of Financial Studies, 1993)
Corporate debt sales have been regarded as “no news” events because there is no significant price reaction on average to their announcement. We explore the hypothesis that this lack of average price reaction to debt sale announcements is explained by the partial anticipation of debt offers. Theory suggests that the demand for debt capital is fundamentally related to changes in the sources and uses of funds, and we find evidence that earnings are significantly lower, investment growth is significantly higher, and, for some issuers, debt refunding requirements are significantly greater in the period immediately prior to issue than in periods well before and after the issue. We find that this preissue information conditions investors’ expectations of issue, thereby affecting the cross-sectional announcement date price reaction to debt sales in two ways. First, announcement date price reactions are negative, on average, for unanticipated offers or for those offers where prior information suggests that an issue is unlikely. Second, holding the probability of issue constant, announcement date price reactions are significantly more negative for offers that raise more capital than investors expected. These results are consistent with cash flow signaling and asymmetric information models of corporate financings.